Recovery from Covid-19 critical illness: a secondary analysis of the ISARIC4C CCP-UK cohort study and the RECOVER trial - Pauley, E; Drake, TM; Griffith, DM; Sigfrid, L; Lone, NI; Harrison, EM; Baillie, JK; Scott, JT; Walsh, TS; Semple, MG; Docherty, AB (SAGE Publications, 2021)
Background: We aimed to compare the prevalence and severity of fatigue in survivors of Covid-19 versus non-Covid-19 critical illness, and to explore potential associations between baseline characteristics and worse recovery.